Improving Extension Curriculum Design Using Learner-Centered Templates - Mary L. Halbleib ([TEST] Journal of Extension, 2021)
Extension professionals’ use of learner-centered instructional practices can maximize engagement and more effectively address expressed needs within their diverse communities. The Outcome-Based Extension Education Design and Facilitating Teaching and Learning templates enable educators to effectively implement curricula that identify context-specific learner needs, activities that increase learner engagement, and assessment tasks that gather evidence of essential knowledge construction and skills development. Using these two practical tools, Extension professionals can streamline the creation of compelling and efficacious programs that focus on the intended learning outcomes.
Keywords: professional development; program development; instructional design; teaching; active learning